Effects of tibolone on plasma homocysteine levels in postmenopausal women - Celik, H; Ayar, A; Tug, N; Cikim, G; Kilic, N; Parmaksiz, C (Elsevier Science Inc, 2002)
Objective: To investigate the effects of tibolone on levels of plasma homocysteine, an independent risk factor for cardiovascular disorders, in postmenopausal women. Design: Prospective, randomized clinical study. Setting: University hospital. Patient(s): Postmenopausal healthy women. Intervention(s): Tibolone (2.5 mg/d) or calcium (1250 mg/d) and conjugated equine estrogens (0.625 mg/d) plus medroxyprogesterone acetate (5 mg/d) were administered orally for 6 months. Blood samples were collected at the start and the end of therapy. Main Outcome Measure(s): Plasma homocysteine levels. Result(s): Administration of tibolone and calcium caused only a 4% decrease in plasma homocysteine levels compared with initial levels. In contrast, conjugated equine estrogens plus medroxyprogesterone acetate caused a 29% decrease in plasma homocysteine levels. Conclusion(s): Despite the reported beneficial effect of tibolone on the serum lipid profile, tibolone had no statistically significant effect on serum homocysteine levels in postmenopausal women. The possible cardiovascular protective role of tibolone might be unrelated to its effects on homocysteine levels.
Keywords: tibolone; homocysteine; postmenopausal women